Sustainable urban transport - Attard, Maria; Shiftan, Yoram (Bingley, U.K. : Emerald, 2015)
The requirement for sustainable transport in urban areas has become more onerous in the past decade due to a number of negative externalities which have been increasingly associated with growing mobility and the advances made in the technology and available options for sustainable transport. However, whilst on one hand technology has supported the reduction of environmental impacts of increased (car) mobility, other policies and actions influencing behaviour have been identified as key contributors to reduce the impact of transport. While the intentions behind particular policies point towards sustainability goals, attitudes towards mode choice are proving more difficult to shift. Specific actions are driving best practice in reducing car dependence by providing alternative means of car sharing and public transport use, whilst others look at promoting non-motorized forms of transport. This publication brings together an international group of researchers and presents work from different countries dealing with issues related to transport policy, attitudes and mode choice, car sharing and alternative modes of transport, and discusses the future of non-motorized modes of transport.
Sustainable urban transport : an introduction / Maria Attard, Yoram Shiftan -- The economic assessment of health benefits of active transport / Elisabete Arsenio, Paulo Ribeiro -- Mode decisions and context change : what about the attitudes? A conceptual framework / Annika Busch-Geertsema, Martin Lanzendorf -- The influence of parent's perceptions and residential self-selection to the children's travel modes at single parent households / Yusak O. Susilo -- Children's independent mobility in Israel : case study of the Arab population group / Wafa Elias -- The Malta bus service reform : implications for policy from a natural experiment of attitudes towards bus service quality, and modal shift / Thérèse Bajada -- Further research into using geographic principles to analyze public transportation in the USA and maximize the concept of induced transit / Richard D. Quodomine -- Understanding multimodal and intermodal mobility / Helga Jonuschat, Korinna Stephan, Marc Schelewsky -- Who would use integrated sustainable mobility services and why? / Daniel Hinkeldein [and others] -- Car sharing systems as a sustainable transport policy : a case study from Lisbon, Portugal / Patrícia Baptista, Sandra Melo, Catarina Rolim -- Analysis of effects resulting from improved vehicle fuel efficiency and fuel price changes applied to the Berlin city network / Arne Höltl, Matthias Heinrichs, Cathy Macharis.
Print version record.
Includes bibliographical references and index.
Keywords: Urban transportation -- Environmental aspects; Urban transportation policy; City planning; Sustainable urban development; Urban transportation policy; Urban transportation; Transportation -- General; Sustainability; Transport planning & policy; BUSINESS & ECONOMICS -- Industries -- Transportation; TRANSPORTATION -- Public Transportation; Urban transportation -- Environmental aspects; Urban transportation policy; Electronic books